1999
DOI: 10.1139/x99-056
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between growth and growth rhythm observed in a short-term test and performance in long-term field trials of Norway spruce

Abstract: Genetic parameters were estimated for traits observed in one short-term "farm-field" test and in seven long-term field trials of Norway spruce (Picea abies (L.) Karst.). The trials, located in southern and central Sweden, were based on subsets of 201 open-pollinated families derived from plus trees grafted in seed orchards. Observations of height growth and phenology in the farm-field test were made during years 2-4, and trees in field trials were assessed for height and damage at 9-14 years of age. Narrrow-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 27 publications
4
36
2
Order By: Relevance
“…In Norway spruce, date for bud flushing was slightly negatively genetically correlated with 24-year field volume (SONESSON et al, 2002). In addition, in Norway spruce, different stages of bud flushing were slightly negatively correlated genetically with 9-14-year field height (HANNERZ et al, 1999). Thus, lack of strong greenhouse-field correlation observed in this study is consistent with what has been observed in other spruce trials.…”
Section: Greenhouse-field Correlationssupporting
confidence: 90%
“…In Norway spruce, date for bud flushing was slightly negatively genetically correlated with 24-year field volume (SONESSON et al, 2002). In addition, in Norway spruce, different stages of bud flushing were slightly negatively correlated genetically with 9-14-year field height (HANNERZ et al, 1999). Thus, lack of strong greenhouse-field correlation observed in this study is consistent with what has been observed in other spruce trials.…”
Section: Greenhouse-field Correlationssupporting
confidence: 90%
“…However, the timing of flushing for the families should be quite similar at Nilsrud, as strong relationships generally are present between flushing scores at multiple sites (Skrøppa and Steffenrem 2015). The heritability is somewhat lower than the estimates found for flushing scores in other progeny tests (e. g. Hannerz et al 1999;Skrøppa and Steffenrem 2015). The observed genetic correlation between the timing of flushing and C. polonica lesion lengths corresponds to what was found by Krokene et al (2012) who concluded that the level of susceptibility to this pathogen is related to tree phenology.…”
Section: Discussionmentioning
confidence: 82%
“…For Norway spruce, a similar project is underway; however as a secondary tree species, growth rhythm is a particularly important factor for adaptation to a changed climate. Studies have shown that genotypes/provenances with early bud-burst are damaged if exposed to late spring frost events in southern Sweden, resulting in reduced vitality, quality and growth (e.g., [77,96]). In addition, it is predicted that the risk of frost damage to Norway spruce in southern Sweden will increase with climate change due to the earlier occurrence of bud burst in the spring when the nights are still long with a high risk of ground surface radiative cooling [97,98].…”
Section: Adaptations Beyond General Forest Management (In Tree Breedimentioning
confidence: 99%